Get programming with JavaScript Next : new features of ECMAScript 2015, 2016, and beyond - Isaacks, J. D. (Manning Publications, 2018)
"Get Programming with JavaScript Next introduces you to the new features included in the ES2015-and-later JavaScript releases. You'll learn example by example in 34 short lessons, each designed to drive home a specific skill. The coverage is complete: you'll explore new language syntax, declarations, and data types. You'll structure code with modules, replace callbacks with promises, and use classes instead of constructors. Every time you turn a page, complete an exercise, or study a carefully crafted illustration, you'll be one step closer to JavaScript mastery."--